Characterization of tin-plated steel - Pandey, Shatrudhan; Mishra, Karan Kumar; Ghosh, Pampa; Singh, Abhishek Kumar; Jha, Sanjay Kumar (Frontiers in Materials, 2023)
Tinplating on steel is a useful industrial process extensively used for food packing. Cold rolled annealed steel coated with a pot gives the steel corrosion resistance property and a beautiful luster. Tinplating on steel is a complex process called rolled and annealed steel sheets that are clean corollaries with acid to remove rust, grease, or oil from the surface. The pure tin is electrodeposited on this freshly prepared surface after the electrodeposition of tin on the steel strip; the surface becomes grace, the color of pure tin; the finish is called matte. Very often, a flowing heat treatment is just about the tin melting point of 232°C - 265°C. After electrodeposition, pure tin has deposited on the steel surface; however, a chemical reaction between tin and iron occurs during the brightening treatment. This results in the formation of iron tin intermetallic formation; their orientation grain structure and orientation of substrate steel all have a synergistic effect on the final properties of tin-coated steel. In the present study, an attempt has been made to study this parameter in detail. A total of five commercially produced tinplated steel have been selected for the present purpose both tin coating and substrate steel have been thoroughly characterized using optical microscopy, Scanning Electron Microscopy (SEM), and X-Ray Diffraction (XRD), and Crystallographic texture point of view, however, the best result has been discussed in this paper. The different phases of the tin and iron tin compound have been identified using XRD, X-Ray, and Texture goniometer used to find out the crystallographic texture observed presence of FeSn2, FeSn, and Sn has been found in the tin coating; the volume fraction of this phases is observed to vary from one sample to another. This variation may affect tinplating steel’s final property, which can be studied in future work.